Does Orthokeratology Wearing Affect the Tear Quality of Children? - Tao, Zhengyang; Wang, Jiao; Zhu, Minjuan; Lin, Zhihong; Zhao, Jun; Tang, Yu; Deng, Hongwei (Frontiers in Pediatrics, 2022)
Orthokeratology is currently known as one of the most effective methods of myopia control in the process of rapid deterioration of the global myopia prevalence. As orthokeratology is widely used, it is necessary to evaluate its complications reasonably and accurately. Eye surface problems in children, such as dry eyes, have received increasing attention. At present, there is no conclusive evidence on how orthokeratology affects the ocular surface, especially the tears. To our knowledge, this is the first study to explore the relationship between orthokeratology lenses and tears through meta-analysis. However, it is still challenging to get a convincing conclusion and a higher level of evidence in this meta-analysis. Reasons for this include limitation of study design, lack of clarity on important confounding factors, lack of appropriate statistical tools, and other biases. This paper will analyze the dilemma existing in the current research from different perspectives to provide meaningful information for future studies in this field.